Analysis of Adolescents Consumer Interest In Purchasing Frozen Food Products For Vocational School X Students In East Jakarta - Khoirul Anwar; Jihan Fitriyah (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2023)
Imbalanced nutritional intake in adolescents is one of the causes of overnutrition problems. Adolescents diet trends that like easy, practical and economical food such as Frozen Food. The aim of this research is to analyze adolescents consumers' interest in purchasing frozen food products in East Jakarta. This research uses a cross-sectional method design. Location The research was conducted at SMK X in East Jakarta. The sample taken by this researcher used a purposive non-probability sampling technique. The sample size in the study was 60 respondents. The data collected is a description of consumer interest in frozen food, and food consumption patterns using a Food Frequency Questionnaire (FFQ). The research results show that adolescents often consume Frozen Food in the categories of processed fish, processed poultry and processed bakery. Based on consumer interest analysis, 55.0% of respondents strongly agree that there is an expiration date in product information, 58% of respondents agree that price is a consideration for purchasing. Apart from that, respondents strongly agree to buy frozen food products because they are practical (31.7%), long shelf life (31.7%), appetizing (16.7%), and packaging (18.3%). The conclusion of this research is that adolescents are interested in frozen food due to many factors, such as price, shelf life, practicality and packaging. The type most widely consumed is Frozen Food in the animal protein category.